Literature Review The Effect of Organizational Internal Control, Leadership Style and Organizational Commitment on Managerial Performance - Mahaputra, M. Ridho (Dinasti Research, 2021)
The Literature Review article on the Effect of Organizational Internal Control, Leadership Style and Organizational Commitment on Managerial Performance is a scientific article that is useful in building research hypotheses regarding the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Organizational Internal Control has an effect on Managerial Performance; 2) Leadership Style has an effect on Managerial Performance; and 3) Organizational Commitment has an effect on Managerial Performance. Apart from these 3 exogenous variables that affect managerial performance endogenous variables, there are other factors including motivation, management control system and skills.